SCALING SMART VALLEYS APPROACH FOR LAND AND WATER MANAGEMENT: INSIGHTS AND LESSONS LEARNED FROM 2022 TO 2025 - Suh, Neville Ndohnwi; Djagba, Justin; Dossou Yovo, Elliott Ronald (2025)
Rice production is rapidly increasing in Mali. However, population growth continues to outpace rice production, raising concerns about whether Mali can reach its goal of rice self-sufficiency. Additionally, rice production systems in Mali are vulnerable to the combined effects of recurring extreme weather events and the lack of co-designed relevant adaptation strategies. Without proper climate-smart agricultural (CSA) strategies, considerable yield declines have been reported in rice fields, with projections indicating that these declines may worsen in inland rice production systems. Hence, there is a need to continuously promote the widespread access and use of context-specific CSA innovations, such as the Smart Valleys' approaches to inland water management, which is key to enhanced rice productivity. Since 2022, the AICCRA Mali project has been promoting the dissemination of various CSA innovations in rice-based systems in Mali, particularly by engaging local partners who directly provide capacity-building and agro-advisory services to farmers. Between 2022 and 2025, 54 Smart Valleys have been developed in rice production systems in Mali, supporting the rice production activities of over 4500 rice farmers, about 84% of whom are female. The main objective of this workshop is to enhance and strengthen the capacity of different actors engaged in rice value chains on site selection, development, and post-development maintenance of Smart Valleys in inland rice production systems. The workshop also identified various constraints faced in adopting the Smart Valleys approach to water management. To ensure the ongoing expansion of the AICCRA initiative, key lessons and insights from implementing the AICCRA project between 2022 and 2025 were highlighted by workshop participants, which are essential for promoting sustained scaling of Smart Valleys in Mali.